Spatial distribution and habitat suitability of Biomphalaria straminea, intermediate host of Schistosoma mansoni, in Guangdong, China - Ya Yang; Shao-Yu Huang; Fu-Quan Pei; Yue Chen; Qing-Wu Jiang; Zhuo-Hui Deng; Yi-Biao Zhou (BMC, 2018)
Abstract Background Biomphalaria straminea is an invasive vector in China, posing a significant threat to public health. Understanding the factors affecting the establishment of this snail is crucial to improve our ability to manage its dispersal and potential risk of schistosomiasis transmission. This study sought to determine the spatial distribution of B. straminea in mainland China and whether environmental factors were divergent between places with and without B. straminea. Methods A malacological survey of B. straminea was conducted in Guangdong Province, China. Snails were identified using anatomical keys. Water and sediment samples were taken, and their physicochemical properties were analyzed using national standard methods. Landscape and climatic variables were also collected for each site. We compared the environmental characteristics between sites with and without B. straminea using Mann-Whitney U test. We further used generalized linear mixed models to account for seasonal effects. Results B. straminea was found at six sites, including one in Dongguan and five in Shenzhen. Probability map found a hot spot of B. straminea distribution at Shenzhen and Hong Kong. Sites occupied by B. straminea were characterized by higher median altitude, mean annual precipitation and moderate temperature. Water with snails had higher median concentrations of total nitrogen, nitrate and nitrites, ammoniacal nitrogen, calcium, zinc and manganese but lower dissolved oxygen and magnesium. Sediments with snails had higher median copper, zinc and manganese. B. straminea was associated with maximum temperature of the warmest month (pMCMC < 0.001) and sediment zinc (pMCMC < 0.001). Conclusions B. straminea is distributed in Shenzhen and its surrounding areas in Guangdong, China. Sites with and without B. straminea differed in the maximum temperature of the warmest month and sediment zinc. Surveillance should be continued to monitor the dispersal of this snail in China.